Towards a Law of the Mammoth? Climate Engineering in Contemporary EU Environmental Law. (March 2016) - Somsen, Han
Abstract : In an article that made waves when it was first published in 1996, judge Easterbrook scorned the idea that the technological reality of cyberspace justified talk about or a need for 'Cyber Law'. Just as there is no need for a 'Law of the Horse' merely because horses give rise to legal claims, he argued, conventional legal principles and reasoning are sufficiently accommodating to absorb new legal challenges that arise in the wake of cyberspace. We may likewise doubt the need for a 'Law of the Mammoth', even though technologies emerge that harbour the prospect of bringing back the woolly mammoth from extinction, reversing climate change, and creating new life forms. Cyber Law is now firmly established, of course, and Easterbrook also appears to have lost the academic debate from the likes of Lawrence Lessig. That fact notwithstanding, the onus to show that the time has come for a Law of the Mammoth clearly is on those staking the claim.